PENGARUH KEBIJAKAN DIVIDEN, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN (StudiKasusPada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2016) - Tri Yuliyanti, 14.05.62.0001; Kartika, Andi (Students' Journal of Accounting and Banking, 2018)
This study aims to analyze the effect of dividend policy, liquidity, profitability, firm size and leverage on firm value. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2013-2016. The sample in this study was taken by using purposive sampling technique to obtain a sample of 173 companies. The data analysis tool used in this study is descriptive analysis and multiple regression analysis. The results of this study indicate that dividend policy, liquidity does not affect the value of the company, and profitability, firm size, leverage has a significant positive effect on the value of the company. Keywords: Dividend Policy, Liquidity, Profitability, Leverage Company Size, Company Value.